Edukasi Sampyong untuk Menguatkan Eksistensi Kesenian Tradisional di Majalengka - Mohamad Solehudin Zaenal; Hilman Firmansyah; Nidia Haiva Agustina; Evi Silviana Heryanti; Maulana Yusuf Ibrahim; Farida Hanum (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2016)
Sampyong is a traditional art in Majalengka, West Java. It is a local dance which presents the attraction of courage and dexterity. This art has been an attraction at the celebrations in the community since long time ago. But nowadays, the existence of Sampyong has been faded. One of the effort to preserve Sampyong is through Sampyong Educational activities, especially for high school students as young generation. These activities  include “Naon eta Sampyong?”, Techniques of Sampyong, Terlarut, Sampyong Art Festival, and the Inauguration of Extracurricular by the school as a results of the program implementation. These activity has been held at SMAN 1 Maja in Majalengka. The target of this activities is 15 senior high students. The results of the program are increasing of student knowledge, student’s interests and student’s skill in play Sampyong. Strengthening the Sampyong as Majalengka icon and granting the Sampyong art as national cultural heritage will be the sustainability of this program.